Entre el mecapal y el cielo : desarrollo del movimiento mayo en Guatemala - Bastos, Santiago; Camus, Manuela (Guatemala, C.A. : Facultad Latinoamericana de Ciencias Sociales (FLACSO) ; Guatemala, C.A. : CHOLSAMAJ, 2003)
A study of the Mayan movement during 1995-2002, updating the author's two previous volumes "Quebrando el Silencio" and "Abriendo Caminos". This study focuses on popular participation, the group COPMAGUA, electoral activities and international cooperation.
Includes bibliographical references (p. 335-347).
Keywords: Coordinación de Organizaciones del Pueblo Maya de Guatemala -- History; Mayas -- Guatemala -- Government relations; Mayas -- Guatemala -- Politics and government; Mayas -- Legal status, laws, etc. -- Guatemala